Socio-Demographic Factors in Predicting Organizational Commitment of Nepal Telecom Employees - Jain, Bandana Kumari; Lamichhane, Krishna Kumar (Management Dynamics, 2020)
The study intends to assess the 3-dimensional organizational commitment and its effects on socio-demographic factors such as gender, age, and tenure of Nepal Telecom employees. Random sampling method proportionately to the job position level had been harnessed to collect primary data with survey method and ultimately, 322 samples were gathered. Analysis tools t-test, ANOVA, post hoc analysis harnessed to examine the objectives. The study results that age and work experience are significantly associated to employees’ normative commitment while higher working years of employees are different from less experiential employees in terms of overall commitment and continuance commitment.